Analysis of the Novel by V. Mikhailov “The Chronicle of the Great Jute” in University Auditorium (Journal of Educational Sciences, 2019)
The article discusses the methodical ways of parsing the story of V. Mikhailov «Chronicle of the Great Jute». To study the poetics and problems of the story, it is advisable to use some of the techniques of the methodical plan. When studying the story «The Chronicle of the Great Jute», the author of the article tested various types of projects. Students in the course of formative training carried out the following projects: they explored certain aspects of the poetics of the story (research projects), created essays (creative projects), conducted an innovative game (role-playing projects), prepared reports (information projects), compiled short dictionaries of theoretical concepts -oriented projects). When studying the story of V. Mikhailov «The Chronicle of the Great Jute», the method of integrating literary studies with the history of Kazakhstan was also used. As is known, without students mastering theoretical concepts and their skillful application in the analysis of a literary work, their philological development is impossible. Cataloging educational material is an effective methodical technique, which made it possible to successfully form theoretical representations of students when studying the story «The Great Jute». In the course of training, the reception of programmed teaching was successfully applied – the compilation of literary theses summarizing the content of V. Mikhailov’s Chronicle of the Great Jute. In the process of the formative experiment, the elements of block-module training were also used. All educational material was divided into separate blocks: theoretical, practical, textual. Key words: teaching methods, personality-oriented learning, activation of thinking, project method, integration of objects, cataloging, genre structure, V. Mikhailov, the story «The Chronicle of the Great Jute».